Laterality frequency, team familiarity, and game experience affect kicking-foot identification in Australian football players - Moore, B. B.; Adams, R. D.; O'Dwyer, N. J.; Steel, K. A.; Cobley, S. (International Journal of Sports Science & Coaching, 2017)
This study examined whether laterality frequency, team familiarity, and game experience affected preferred kicking foot identification in professional Australian Football players. Using a repeated-measures experimental design, 13 and 10 players, respectively, identified the kicking foot of 30 teammates and 30 opponents using static images in a randomised sequence. Accuracy (%), reaction time (RT ms), and discrimination capability indices were examined. Overall, participants were less accurate and had slower reaction times when identifying the kicking foot of opposing team players relative to the speed and accuracy of identifying teammates. Significantly lower discrimination accuracy was also evident in participants' capability to identify left-footed players from two different opposing teams. In moderating trends, opposing player game experience was correlated with accuracy and reduced reaction times, while participant game experience correlated with faster reaction times only. Laterality, (opposing) team familiarity, and game experience affect kicking foot identification in Australian Football with training and performance implications. ABSTRACT FROM AUTHOR